Envío de electrocardiograma a través de internet usando un electrocardiógrafo acoplado a una computadora personal - Yapur, Miguel (2009)
The present Project was implemented with the goal of helping the Manglaralto community and its neighbouring towns through the Santa María del Fiat Foundation, for emergency electrocardiograms when no cardiologist is present to review the examination. The Foundation does not count on a physical cardiologist, but instead utilizes the help of a specialist, who visits the Foundation every 45 days to assist patients. Because of this fact, the necessity to implement a telemedicine team for emergencies became clear and will help replace the physical presence of the specialist in Manglaralto. The project consists of taking the analog starting signal of an electrocardiograph (EKG), in order to process it and digitize it; the signal is received through the parallel port of a personal Computer (PC) situated near the electrocardiograph. It’s read through a software installed on the PC with Internet access and, thus is able to send the electrocardiogram, in image format to the E-mail account of the cardiologist of the Foundation.